Clínica Médica e Cirúrgica de Ruminantes e Equídeos: Deslocamento de Abomaso á Direita. - Georgetti, Emerson Danillo da Silva (Universidade Federal do Tocantins, 2023)
The curricular supervised training required was held in Bovine Clinic of Garanhuns, Federal Rural University of Pernambuco and passed between 06/01/15 to 07/31/15 contemplating a workload of 352 hours, looking at the medical clinic areas of ruminants , medical clinic of equine surgical clinic of ruminants and horses and clinical analysis laboratory under the supervision of the veterinarian Luiz Teles Coutinho and guidance of Prof. Dr. Michel José Sales Abdalla Helayel. They were followed a total of 152 cases between medical and surgical during the period, and monitoring of 69 laboratory tests, ultrasound exams 22 and 25 necropsies. The aim of the internship was to strengthen the knowledge acquired during the graduation and apply them in practice in a large sample routine, it is important the interaction with professionals and interaction with owners. In this paper will address a case accompanied during the probationary period, right displacement of the abomasum.